2014
DOI: 10.22146/gamaijb.5354
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Relational Reward Benefits for Developing the Non-Financial Value of a Customer to an Organization: Structural Equation Modeling Approach

Abstract: Abstract:Research on the customer value to an organization has been widely explored, yet most studies only determined on the financial value based on the customer's purchasing behavior. The value of customers beyond their purchasing behavior -defined as the relational worth -has not been commonly captured yet. This non-financial value is one of the drivers in retaining customers, hence it becomes a crucial factor in preserving the profitability of the organization. For this reason, this paper aims to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…It is still unknown if these programs contribute to the key performance indicators in airline industry. These indicators are firm revenue, profit streams and the number of passengers carried (Gittell et al, 2004;Carlsson & Lofgren, 2006;Lederman, 2007;Wong & Chung, 2008;Demydyuk, 2011;Kristiani et al, 2014;Olazabal et al, 2014). Prior research (Berman, 2006;Bagdoniene & Jakstaite, 2007;Liu & Yang, 2009;Omar et al, 2010;Huettinger & Cubrinskas, 2011;Omar et al, 2011aOmar et al, , 2011b has shown that loyalty program has become an important mechanism to increase firm revenue.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It is still unknown if these programs contribute to the key performance indicators in airline industry. These indicators are firm revenue, profit streams and the number of passengers carried (Gittell et al, 2004;Carlsson & Lofgren, 2006;Lederman, 2007;Wong & Chung, 2008;Demydyuk, 2011;Kristiani et al, 2014;Olazabal et al, 2014). Prior research (Berman, 2006;Bagdoniene & Jakstaite, 2007;Liu & Yang, 2009;Omar et al, 2010;Huettinger & Cubrinskas, 2011;Omar et al, 2011aOmar et al, , 2011b has shown that loyalty program has become an important mechanism to increase firm revenue.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, B. P. S. Murthi et al (2011) found surprising evidence that in credit card industry customers who participate in loyalty program generate significantly less profit than those customers who do not. In airline industry the situation is opposite: frequent flyer programs do contribute to the profit of an airline (Kristiani et al, 2014). Formally, we offer the following hypothesis: H2: holding a loyalty program ensures a higher profit for an airline.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation